Acid mine drainage, rock drainage, and acid sulfate soils : causes, assessment, prediction, prevention, and remediation - Jacobs, James A. 1956-; Lehr, Jay H., 1936-; Testa, Stephen M. (John Wiley & Sons, Inc., 2013)
Written to help readers understand the formation of AMD, Acid Mine Drainage addresses the generation of acidic waters usually from both used and abandoned coal or metal mines. Offering the most up-to-date ideas on metals remediation, which makes finding control methods relatively easy, the text provides a section on legal and policy issues and details the causes, control, prediction, prevention, and remediation of AMD formation. Case studies from North America, Europe, Asia, and developing countries highlight various approaches to AMD problems.